2008
DOI: 10.1111/j.1600-6143.2008.02431.x
|View full text |Cite
|
Sign up to set email alerts
|

Natural Killer Cell Receptor Repertoire and Their Ligands, and the Risk of CMV Infection After Kidney Transplantation

Abstract: Cytomegalovirus (CMV) infection is the most common viral complication after solid organ transplantation (SOT). Whilst current immunosuppression is knownto impair antiviral-specific T-cell immunity in SOT, a potential role for natural killer (NK) cells not affected by immunosuppressive therapy remains to be determined. To address this, we compared the genotype of the NK immunoglobulin-like receptor (KIR) genes and their HLA cognate ligands to the rate of CMV infection in 196 kidney transplant recipients. We hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
68
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(73 citation statements)
references
References 59 publications
(100 reference statements)
3
68
2
Order By: Relevance
“…The current literature on CMV infection and NK cell function is tilted overwhelmingly towards studies of solid organ and haematopoietic cell transplantation where patients are severely immunocompromised or elderly [23,32,39,40]. In CMV infection enhances NK cell activity 1 NK cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The current literature on CMV infection and NK cell function is tilted overwhelmingly towards studies of solid organ and haematopoietic cell transplantation where patients are severely immunocompromised or elderly [23,32,39,40]. In CMV infection enhances NK cell activity 1 NK cells.…”
Section: Discussionmentioning
confidence: 99%
“…1 NK cells help protect against CMV, as an increased proportion of these cells is associated with a lower risk of acute CMV infection in patients undergoing solid organ transplantation [23], and NKG2C…”
Section: Introductionmentioning
confidence: 99%
“…This effect is likely limited in vivo in most cases by the dilution of PLT-Ecto; however, at the time of allogeneic stem cell transplantation, PLT are often transfused in large amounts precisely at the time when the transplanted patients primarily need NK cell activity to prevent posttransplant viral infections and to exert an antitumoral effect (47)(48)(49). The decrease of the number of PLT-Ecto during transfusion can be achieved by transfusing very fresh PLT (the release of Ecto increases with storage time).…”
Section: Discussionmentioning
confidence: 99%
“…7). Several studies have reported an association between the KIR and HLA genotype and the development of CMV infection following hematopoietic stem cell (37) and solid-organ (38,39) transplantation. Moreover, a recent study (22) showed increased susceptibility to developing symptomatic primary CMV infection in immunocompetent adults carrying an AA haplotype or the HLA-Bw4 T allele.…”
Section: Discussionmentioning
confidence: 99%